Influence of dietary lysine on carcass characteristics of high-lean growth gilts fed from 80 to 160 lb - K G Friesen; B J Kerr; Jim L Nelssen; Robert D Goodband; Michael D Tokach; John A Unruh; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1993)
Seventy-two high-lean growth gilts (initially 75.5 lb BW) were used to determine the influence of dietary lysine on carcass characteristics at 120 and 160 lb. Gilts were randomly selected for slaughter when the average weight of pigs in the pen equaled or exceeded 120 and 160 lb. The experiment was designed as a randomized complete block, with initial weight serving as the blocking factor. Six dietary treatments were included, ranging from .54 to 1.04% digestible lysine (.69 to 1.25% total dietary lysine). At 120 lb, hot carcass weight decreased and then increased as did dressing percentage for gilts fed increased dietary lysine. Average backfat thickness and 10th rib fat depth were not influenced by dietary treatment. However, longissimus muscle area (loineye) was increased for gilts fed greater dietary lysine. Kidney fat and total carcass lipid decreased but carcass moisture increased as dietary lysine increased. The decreased carcass lipid content resulted in reduced longissimus muscle marbling at 120 lb. For gilts fed to 160 lb, hot and chilled carcass weight decreased and then increased as dietary lysine increased. Dressing percentage followed a similar pattern because of the difference in carcass weight. Backfat thickness, 10th rib fat thickness, and kidney fat decreased for gilts fed increased dietary lysine. Carcass moisture and crude protein increased and then decreased as dietary lysine increased. The moisture content was maximal for gilts fed .94% digestible lysine, whereas carcass crude protein was maximal for gilts fed .74% digestible lysine. However, carcass lipid followed an opposite pattern, decreasing and then increasing as dietary lysine increased. Carcass muscle score improved but longissimus muscle marbling decreased for gilts fed greater dietary lysine. The data from this experiment suggest that the high-lean growth gilt requires at least 18 and 22 g/d lysine intakes from 80 to 120 and from 120 to 160 lb, respectively, to optimize longissimus muscle area and minimize carcass lipid content.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Pigs; Genotype; Gilts; Carcass characteristics